Dwarfing mechanisms of Prunus species as interstems and rootstocks on peach [Prunus persica (L.) Batsch] tree vegetative growth and physiology - Weibel, Antonio Marcelo (Clemson University, 2020)
Tesis para obtener el grado de Doctor of Philosophy Plant and Environmental Sciences, de Clemson University, diciembre 2008